First Evidence of Lamprophyric Magmatism from the Konya Region, Turkey: a Genetic Link to High-K Volcanism - Asan, Kursad; Erturk, M. Ali (Wiley, 2013)
In the vicinity of Konya (Turkey), mafic, micro-porphyritic sub-volcanic rocks intrude into the Mesozoic units, which represents the only example of such a rock type in the region. 40Ar/39Ar dating of two whole rock samples from the sub-volcanics gave ages of 13.72 +/- 0.13 and 12.40 +/- 0.11 Ma, suggesting temporal association to the Late Miocene-Pliocene high-K calc-alkaline volcanism in the region. The mineral chemistry and geochemical data permit us to classify the rocks as minette lamprophyres. They include diopside and phlogopite phenocrysts in a microcrystalline groundmass composed of sanidine, phlogopite, diopside and titano-magnetite. Segregation and ocelli-like globular structures occur commonly in the samples. In terms of major elements, the lamprophyres are calcalkaline, and potassic to ultrapotassic rocks. All the lamprophyres display strong enrichments in LILE (Rb, Ba, K, Sr), radiogenic elements (Th, U) and LREE (La, Ce) and prominent negative Nb, Ta, and Ti anomalies on primordial mantle-normalized trace element diagrams. Geochemical data suggest that the lamprophyres and high-K calc-alkaline rocks in the region derived from a subduction-modified lithospheric mantle source affected by different metasomatic events. Lamprophyric magmatism sourced phlogopite-bearing veins generated by sediment-related metasomatism via subduction, but high-K calc-alkaline magmas are possibly derived from a mantle source affected by fluid-rich metasomatism.
Keywords: Turkey; Konya; calc-alkaline; lamprophyre; minette; metasomatism